Effectiveness of Chitosan and Ariid Catfish Swim Blader Gelatine as Edible Coating on the Preservation of White Shrimp Litopenaeus vannamei - Susanto, Eko; Martiyana, Sri; Purnamayati, Lukita (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2025)
White shrimp (Litopenaeus vannamei) is a high-value fishery commodity that is highly perishable due to rapid microbial growth, enzymatic activity, and lipid oxidation during storage. Chitosan is widely recognized for its antimicrobial and antioxidant properties, while gelatine derived from Ariid catfish swim bladders represents an underutilized fishery by-product with excellent film-forming, gelling, and oxygen-barrier properties. This study aimed to evaluate the effectiveness of a composite edible coating based on shrimp chitosan and Ariid catfish swim bladder gelatine at different ratios in preserving the quality of white shrimp during chilled storage. Treatments consisted of chitosan–gelatin ratios of K (0:0), P1 (3:7), P2 (5:5), and P3 (7:3), with storage durations of 0, 24, 48, and 72 hours. Quality parameters assessed included thiobarbituric acid (TBA), total plate count (TPC), peroxide value (PV), total volatile basic nitrogen (TVBN), pH, weight loss, sensory attributes (appearance, texture, odor), and melanosis. The results demonstrated that edible coating application significantly affected TBA, TPC, PV, TVBN, pH, sensory quality, and melanosis (p 0.05), while no significant effect was observed on weight loss. The chitosan–gelatine coatings effectively inhibited microbial proliferation, oxidative degradation, and enzymatic activity, thereby extending shrimp freshness. The P3 formulation (7:3) showed the most optimal preservation performance, with TPC of 59.33 × 10³ CFU/g, PV of 3.33 meq/kg, TVBN of 24.31 mg N/100 g, pH of 7.14, and a melanosis score of 2.82 after 72 hours of storage. The synergistic combination of shrimp chitosan and Ariid catfish swim bladder gelatine provides an effective, biodegradable edible coating for extending the shelf life of white shrimp. This study highlights the potential application of fishery by-products as functional biopolymers, contributing to sustainable seafood preservation, value-added processing, and circular bioeconomy development.